TRANSFORMASI HUKUM PIDANA INDONESIA: ANALISIS HISTORIS, TEORETIS, DAN PRAKTIS TERHADAP SISTEM PIDANA NASIONAL - Sugiarto S., Alief (Universitas 17 Agustus 1945 Samarinda, 2025)
Indonesian criminal law has undergone a long journey from the colonial era to the era of modern legal reform. The codification of criminal law in the form of the Criminal Code (KUHP) is a colonial legacy that remains the main reference in the criminal justice system, despite undergoing numerous changes through sectoral laws. This study aims to comprehensively analyze the transformation of Indonesian criminal law from historical, theoretical, and practical perspectives. Through a juridical-normative and descriptive-analytical approach, this paper examines the paradigm shift in criminal law from retributive to restorative justice, as well as the challenges in implementing the new National Criminal Code. The results of the study show that although the steps taken to reform criminal law have been progressive, a critical evaluation is still needed in harmonizing local legal values, human rights, and legal globalization.